Polarization‐Tunable Perovskite Light‐Emitting Metatransistor (Adv. Mater. 1/2023). Issue 1 (5th January 2023) - Klein, Maciej; Wang, Yutao; Tian, Jingyi; Ha, Son Tung; Paniagua‐Domínguez, Ramón; Kuznetsov, Arseniy I.; Adamo, Giorgio; Soci, Cesare
Abstract : Light‐Emitting Metatransistors A radically new light‐emitting device concept, the perovskite light‐emitting metatransistor, which enables active tunability of electroluminescence intensity, polarization, and spectrum, is demonstrated in article number 2207317 by Cesare Soci and co‐workers. Monolithic integration of dielectric perovskite metasurfaces in the active region of electrically driven devices offers new routes for light control.